Airlapse Tasteful Dessert / Muhammad Aliff Aminuddin - Aminuddin, Muhammad Aliff (2021)
Airlapse Tasteful Dessert is a “Sole Proprietorship Business” founded by Muhammad Aliff Bin Aminuddin in 2021, which provides sweeties dessert like caramel pudding sweeties. The idea of creating the business’s name came from the owner where Aliff represents the mix name of owner of the founder and dessert represents that the business is ready to provide sweeties for the customers. The name “Airlapse Tasteful Dessert” itself already illustrates that the business will provides sweeties dessert. The founder, Muhammad Aliff is the owner and agent for Airlapse Tasteful Sdn Bhd that provides and sells Airlapse dessert. Most of the sweeties and dessert provided by Airlapse Tasteful Dessert are for people in all categories of ages. The price range is determined by the gradient and packaging for the pudding, but the price is affordable for everyone to buy.